PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR PEMBELAJARAN TEMATIK MATERI KETENTUAN PERNIKAHAN DALAM ISLAM KELAS XI 3 DI SMAN 3 LUMAJANG TAHUN PELAJARAN 2024/2025 - Muhammad Hendra Firmansyah; Hartono; Nurul Hasan (SIRAJUDDIN : Jurnal Penelitian dan Kajian Pendidikan Islam, 2024)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character and understanding of spiritual values. One of the essential topics in the PAI curriculum for Grade XI is "Marriage Provisions in Islam," which is highly relevant for building religious insight and understanding Islamic family life. However, the learning outcomes of Grade XI-3 students at SMAN 3 Lumajang show that only 40% of students meet the Minimum Mastery Criteria (MMC), with the monotony of conventional teaching methods cited as one of the main contributing factors. To address this issue, this study implemented the Cooperative Learning Jigsaw model to enhance students' learning outcomes. This classroom action research was conducted over two cycles, each consisting of planning, implementation, observation, and reflection stages. The study involved 36 students from Grade XI-3, with data collected through learning outcome tests, observations, and interviews. The results showed a significant improvement in student performance, with mastery levels increasing from 40% in the pre-cycle to 63.8% in the first cycle and 91.7% in the second cycle. Besides improving cognitive learning outcomes, students' participation in group discussions and social skills, such as cooperation and communication, also increased. This study concludes that the Cooperative Learning Jigsaw model is effective in enhancing students' learning outcomes, participation, and social skills. The application of this model contributes to the development of innovative teaching methods that align with the needs of students in the classroom.